2010
DOI: 10.4103/0972-2327.70886
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the configuration of the posterior bifurcation of the posterior communicating artery between fetal and adult brains: A study of a Sri Lankan population

Abstract: Objective:The purpose of this study was to examine the degree of contribution from the vertebrobasilar and carotid systems to the origin of the PCA in fetal autopsy brains of last trimester of pregnancy and to compare with published data on the configuration of adult and fetal brains in a population of Sri Lankan origin.Materials and Methods:The external diameter of the PcomA, pre-communicating part (P1), and the post-communicating part (P2) of posterior cerebral artery (PCA) of 34 fetal brain in the last trim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The preterm infants born after 30 weeks' gestation age have more significantly increased prevalence in the bilateral fetal-type origin of the posterior cerebral artery (83.3%) than those infants born before 30 weeks (Malamateniou et al, 2009). We found bilateral adult and fetal (AA and FF) types in 68.18% and 7.27%, respectively, while De Silva et al (2010) noted in 88.8% and 1.3%, respectively in Sri Lankan population. Hendrikse et al (2005) cited literature data that in the circle posterior part, the variant type with a unilateral fetal-type posterior cerebral artery is present on up to 25% of angiograms, and a bilateral fetal-type posterior cerebral artery present on up to 10% of angiograms.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The preterm infants born after 30 weeks' gestation age have more significantly increased prevalence in the bilateral fetal-type origin of the posterior cerebral artery (83.3%) than those infants born before 30 weeks (Malamateniou et al, 2009). We found bilateral adult and fetal (AA and FF) types in 68.18% and 7.27%, respectively, while De Silva et al (2010) noted in 88.8% and 1.3%, respectively in Sri Lankan population. Hendrikse et al (2005) cited literature data that in the circle posterior part, the variant type with a unilateral fetal-type posterior cerebral artery is present on up to 25% of angiograms, and a bilateral fetal-type posterior cerebral artery present on up to 10% of angiograms.…”
Section: Discussionmentioning
confidence: 64%
“…The patients with fetal type could be more prone to develop vascular insufficiency (Van Raamt et al, 2006) or internal carotid-posterior communicating aneurysms (Zada et al, 2008). According to De Silva et al (2010), fetal configuration has been reported in adults at 4% to 46% on the basis of anatomical and angiographic studies, and a higher percentage of on the basis of anatomical studies has been reported in older fetuses and newborns: 35% and 56%, while only a minority of circles showed a transitional configuration, 14% and 20%, respectively. In our adult cases there was not bilateral transitory configuration as in other studies of infants or adults (Riggs & Rupp, 1963;Hartkamp et al, 1999;Malamateniou et al, 2009, De Silva et al, 2010 or fetuses (Van Overbeeke et al, 1991;Vasović et al, 2008a;De Silva et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In that sense present study is unique and could not be compared with others. According to previous literature [4,5,10,12,13] incidences of unilateral fetal type ranges from 6%-25% but in present study it is 33.9% [Table/ Fig-9]. Presence of such embryonic or fetal type communicating artery protects the brain tissue in case of ischemia of vertebrobasilar system and there will be damage of primary visual area of one side without any damage to the other side in occlusion of basilar artery where such unilateral fetal type PCoA is present [14].…”
Section: Discussionmentioning
confidence: 60%
“…Around 22 nd 24 th weeks, the PCoA and / or the P1 may enlarge and either artery get chance to increase its size according to most favourable hemodynamic situation, thus adult or fetal configuration may develop [19]. In 29-40 wk of gestation the prominent configurations becomes adult and fetal types, 53-59% and 33-34% respectively [8,10]. Other opinion suggests that variation of the segmental calibres are due to amplitude of neck movements in later years of life or due to genetic factors [20,21].…”
Section: Embryological Explanationmentioning
confidence: 99%
“…De Silva et al, (2010) 7 concluded that there is a significant shift in the contribution of carotid versus basilar system. In older fetal brains, blood flow from internal carotid artery is more in PCA which changes to gradually more contribution from vertebra-basilar in the adult brains.…”
Section: Discussionmentioning
confidence: 99%